2022
DOI: 10.1093/mnras/stac737
|View full text |Cite
|
Sign up to set email alerts
|

Radio and far-IR emission associated with a massive star-forming galaxy candidate atz≃ 6.8: a radio-loud AGN in the reionization era?

Abstract: We report the identification of radio (0.144–3 GHz) and mid-, far-infrared, and sub-mm (24–850μm) emission at the position of one of 41 UV-bright ($\mathrm{M_{\mathrm{UV}}}^{ }\lesssim -21.25$) z ≃ 6.6–6.9 Lyman-break galaxy candidates in the 1.5 deg2 COSMOS field. This source, COS-87259, exhibits a sharp flux discontinuity (factor >3) between two narrow/intermediate bands at 9450 and 9700 Å and is undetected in all nine bands blueward of 9600 Å, as expected from a Lyman alpha break at z ≃ 6.8. The full… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 176 publications
(242 reference statements)
2
26
0
Order By: Relevance
“…Our template fitting photo-z thus was consistent with the dropout method, and the ML was consistent with a lower-z solution. In agreement with Endsley et al (2022) we found low χ 2 values (χ 2 galaxy = 0.60 and χ 2 AGN = 3.9) indicat-ing good fits, and that the template fitting solution should be reliable 11 . However, for the ML ν/σ 2 = 0.013, indicating that it wasn't excessively extrapolating, so that the ML prediction ought also be reliable.…”
Section: Metricssupporting
confidence: 88%
See 4 more Smart Citations
“…Our template fitting photo-z thus was consistent with the dropout method, and the ML was consistent with a lower-z solution. In agreement with Endsley et al (2022) we found low χ 2 values (χ 2 galaxy = 0.60 and χ 2 AGN = 3.9) indicat-ing good fits, and that the template fitting solution should be reliable 11 . However, for the ML ν/σ 2 = 0.013, indicating that it wasn't excessively extrapolating, so that the ML prediction ought also be reliable.…”
Section: Metricssupporting
confidence: 88%
“…In this section we show how the combined Hierarchical Bayesian method could be used to check the validity of candidate high-z galaxies, where although there are very few high-z training spec-z, the higher accuracy of GPz at lower redshift may give more accurate weighting to low-z solutions. Endsley et al (2022) report the detection of a possible z ∼ 6.8 massive star-forming galaxy. The source, COS-87259, was identified and assigned a redshift using the a Lyman-break narrow-band dropout technique -and is among the COSMOS sources we have analysed.…”
Section: Metricsmentioning
confidence: 96%
See 3 more Smart Citations